Impact of COVID-19 on obsessive–compulsive disorder: A case series - A V Sowmya (Wolters Kluwer Medknow Publications, 2021)
A public health emergency of international concern, novel coronavirus disease (COVID-19), began in Wuhan, China, in December 2019. Since then, it has been caused a pandemic along with serious mental health problems. No other disorder is more vulnerable to the current situation than obsessive–compulsive disorder (OCD). Our case series focuses on the effects of COVID-19 on OCD along with its various manifestations. Most of our patients had exacerbated symptoms during the current situation, but there were also new onset OCD cases triggered by a variety of stressors.